POTENTIAL ANTI-INFLAMMATORY ACTIVITY OF PLUMBAGO ZEYLANICA - Subramaniyan, Vetriselvan; Paramasivam, Velmurugan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To determine the anti-inflammatory activity of dichloromethane extract of Plumbago zeylanica (DMEPZ), and its possible mechanism of action. Methods: Male Wistar rats (180-200 g) under controlled standard conditions (24±1°C, 55-58 humidity and 12 hrs light/dark cycle). The groups were divided into 5 groups (n=6/group) and assigned as positive control, negative control, and standard and two different test dose groups of P. zeylanica. Paw edema induced by subplantar injection of 0.1 mL of carrageenan (suspended in 1% carboxymethyl cellulose) into the right hind paw in all groups except negative control group. Granuloma induced by cotton pellets (10±1 mg) were implanted into groin region of each rat. The groups were divided into 4 groups (n=6/group) and assigned as possitive control, two different test dose groups of P. zeylanica and standard. Results: Oral administration of DMEPZ shown a significant (p<0.05) dose-dependent protection against carrageenan-induced paw edema. At 1st hr, P. zeylanica shown an inhibition effect of edema in the different doses of 250 mg/kg and 500 mg/kg were found to be 28.57 and 31.79%, respectively. At 3rd hrs, the paw edema inhibition was found to be 30.70 and 40.15%, respectively. Diclofenac (25 mg/kg) had effect of 34.10 and 41.73% (p<0.001) inhibition of paw edema at in 1 and 3 hrs. P. zeylanica 500 mg/kg showed percentage inhibition of wet and dry cotton pellet granuloma in rats 55.84% and 47.92%, respectively. Conclusion: Thus, the present study revealed that the DMEPZ offered significant protection against inflammation.